Dopamine inactivation efficacy related to functional DAT1 and COMT variants influences motor response evaluation - Bender, Stephan; Rellum, Thomas; Resch, Franz; Rietschel, Marcella; Treutlein, Jens; Jennen-Steinmetz, Christine; Brandeis, Daniel; Banaschewski, Tobias; Laucht, Manfred (PLOS ONE, 2012)
Background Dopamine plays an important role in orienting, response anticipation and movement evaluation. Thus, we examined the influence of functional variants related to dopamine inactivation in the dopamine transporter (DAT1) and catechol-O-methyltransferase genes (COMT) on the time-course of motor processing in a contingent negative variation (CNV) task. Methods 64-channel EEG recordings were obtained from 195 healthy adolescents of a community-based sample during a continuous performance task (A-X version). Early and late CNV as well as motor postimperative negative variation were assessed. Adolescents were genotyped for the COMT Val158Met and two DAT1 polymorphisms (variable number tandem repeats in the 3′-untranslated region and in intron 8). Results The results revealed a significant interaction between COMT and DAT1, indicating that COMT exerted stronger effects on lateralized motor post-processing (centro-parietal motor postimperative negative variation) in homozygous carriers of a DAT1 haplotype increasing DAT1 expression. Source analysis showed that the time interval 500-1000 ms after the motor response was specifically affected in contrast to preceding movement anticipation and programming stages, which were not altered. Conclusions Motor slow negative waves allow the genomic imaging of dopamine inactivation effects on cortical motor post-processing during response evaluation. This is the first report to point towards epistatic effects in the motor system during response evaluation, i.e. during the post-processing of an already executed movement rather than during movement programming.
Gesehen am 05.04.2018